New Concepts in Diagnosis and Therapy of Pancreatic Adenocarcinoma - Laghi, Andrea; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book adopts a multidisciplinary approach to examine in detail a range of interesting new concepts in the diagnosis and therapy of pancreatic adenocarcinoma. Its primary goals are to offer a valuable source of information for clinicians involved in the management of patients with pancreatic adenocarcinoma and to provide a modern guide to the disease for those who are interested in updating their knowledge, including fellows and senior residents. The book is divided into three parts. The first part provides an epidemiological and clinical overview of the disease, followed by an update on pathological findings, including new discoveries in the area of molecular biology. The second part, on diagnosis, offers detailed and comprehensive information on the advantages and disadvantages of different imaging techniques, including nuclear medicine and endoscopic ultrasound. Each diagnostic strategy is critically reviewed with regard to cost-effectiveness. The concluding part of the book, on therapy, gives a panoramic overview of the various therapeutic options, from surgery to chemotherapy and palliative approaches based on interventional endoscopy and radiology.
Part I: Epidemiology, Clinical Aspects and Pathology: Epidemiology, Risk Factors and Clinical Presentation -- Pathology and Molecular Biology -- Part II: Diagnosis: The Case for US.-The Case for MDCT -- The Case for MRI.-EUS: When and Why -- The Role of PET-CT in Diagnosis, Staging and Follow-Up -- A Cost Decision Analysis for Diagnosis and Staging -- Part III: Therapy: The Case for Surgery -- The Locally Advanced Non-Metastatic Cancer -- The Metastatic Patient: Adjuvant Therapy -- The Role of Interventional Endoscopy -- The Role of Interventional Radiology -- Subject Index.
Keywords: Medicine; Radiology, Medical; Internal medicine; Gastroenterology; Oncology; Abdomen -- Surgery; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Internal Medicine; Abdominal Surgery; Gastroenterology; Oncology